Upaya penatalaksanaan pola nafas tidak efektifPada pasien chronic kidney disease di RSUD Dr. Soehadi Prijonegoro - Firdaus, Reyva Bahtiar; , Ns. Arief W. Jadmiko, S.Kep., M.Kep (2016)
Chronic Kidney Disease is a disorder of renal function undergoing damage and its nature cannot return as before. And the disease can cause death in patients. Symtomps that often arises in people with chronic kidney disease is anemia, oedema, fatigue, shortness of breath. Excess fluid that can cause oedema can be cause due to kidney function that can no longer filter toxins in the body, so the urine comes out is reduce and body fluids will multiply and to inflict of oedema, other sufferers of chronic kidney disease will also experience shortness of breath disorders, it can be caused due to breathing the kussmaul, then due to the fluid that builds up in the lungs and can be caused also the levels of Hemoglobin in the body less than normal and eritropoitin reduced a declining kidney causing a decrease in the levels of Hemoglobin. Objective: The purpose of this research is the author wanted to know the influence of nursing care in a an attempt to overcome ineffective breath pattern for 3 days by the metodh of diskriptive by collecting all the data related to the patient. Methods: The research was made against sufferers of chronic kidney failure in the Tulips hospitals Sragen, author doing research for 3 days by the method of diskriptifby collecting all the data related to the patient. Result: After done actions during 3x24 hours on chronic renal failure patient to seek effectiveness breath pattern by teaching techniques of breath in and sit upright and then bend forward as well as administering oxygen oxygen therapy with a dose of 3 liters by nasal kanul, influence on patients from day one until day three patients still feel shortness of breath and respiratory permenit the number is still above normal values. Conclusion: The Issues in patients with ineffective breathing Pattern is not resolved resolved because when done nursing care during 3x24 hours patients did not experience an increase in the effectiveness of breath patterns in accordance with the criteria of the planned results.